2014
DOI: 10.1016/j.fertnstert.2014.07.1143
|View full text |Cite
|
Sign up to set email alerts
|

Birth outcomes by infertility diagnosis: analyses of the massachusetts outcomes study of assisted reproductive technologies (MOSART)

Abstract: Objective To evaluate ART pregnancy outcomes by infertility diagnosis. Study Design ART data on women who were treated and gave birth in Massachusetts were linked to vital records and hospital utilization data. Live births were categorized by eight mutually-exclusive ART diagnoses. Risks of prematurity, low birthweight (LBW), small-for-gestation (SGA), large-for-gestation (LGA), pregnancy hypertension, gestational diabetes, prenatal hospitalizations, and primary cesarean delivery were modeled using logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 37 publications
1
37
1
Order By: Relevance
“…The subfertile population in that study, identified through a combination of birth certificate information, use of ART for previous deliveries, and hospitalizations that included ICD-9 codes of infertility (9), was not further categorized by specific infertility-related diagnosis. In another study we compared diagnosis categories within the ART population using male factor pregnancies as the reference group and found elevated risks for gestational diabetes and preterm delivery in women with ovulation disorders as well as an increased risk of prenatal hospital admissions for women with endometriosis (5). Diagnoses have also been shown to affect outcome in other studies (12, 13).…”
Section: Discussionmentioning
confidence: 99%
“…The subfertile population in that study, identified through a combination of birth certificate information, use of ART for previous deliveries, and hospitalizations that included ICD-9 codes of infertility (9), was not further categorized by specific infertility-related diagnosis. In another study we compared diagnosis categories within the ART population using male factor pregnancies as the reference group and found elevated risks for gestational diabetes and preterm delivery in women with ovulation disorders as well as an increased risk of prenatal hospital admissions for women with endometriosis (5). Diagnoses have also been shown to affect outcome in other studies (12, 13).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis is part of a larger population-based study of ART in Massachusetts [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The objective of this current analysis is to evaluate the effect of maternal fertility status (fertile, subfertile, or ART) on the pregnancy and birth outcomes in consecutive singleton births.…”
Section: Objectivementioning
confidence: 99%
“…This is the third in a series of analyses evaluating the effect of ART diagnoses and treatment parameters on the course and outcome of pregnancy (13,14). This within-ART set of analyses is part of a larger population-based study of ART in Massachusetts (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Objectivementioning
confidence: 99%
“…This within-ART set of analyses is part of a larger population-based study of ART in Massachusetts (13)(14)(15)(16)(17)(18)(19)(20)(21). The objective of this current analysis is to evaluate the effect of number of embryos transferred (ET) and plurality at the six-week ultrasound (fetal heartbeats, FHB) on the pregnancy and birth outcomes of singleton births, specifically prematurity, low birthweight, and small-forgestational age birthweight.…”
Section: Objectivementioning
confidence: 99%